Charge delocalization in the cascade band structure CdS/CdSe and CdS/CdTe core-shell sensitized with Re(I)-polypyridyl complex - Maity, Partha; Debnath, Tushar; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry C, 2016)
Charge-carrier dynamics of CdS quantum dot (QD) and CdS/CdSe type-I and CdS/CdTe type-II core shell nanocrystals (NCs) sensitized with a Re(I)-polypyridyl complex have been carried with special emphasis on studies on carrier delocalization and the role of Re-complex as a hole acceptor and sensitizer molecule. Our investigation confirmed photoexcited hole transfer from CdS and CdS/CdSe to the Re-complex, while no hole transfer was observed in the CdS/CdTe Re-complex system. This was rationalized by the evaluation of the relative energy levels, which revealed that such hole migration was not energetically favorable due to low-lying highest occupied molecular orbital (HOMO) of the Re-complex as compared with the valence band (VB) of CdTe shell; however, luminescence quenching from upper excited states of Re-complex was observed in the presence of all three QD and core shell systems, which has been attributed to electron injection from hot state (energetically higher than the LUMO state) of the Re-complex to the conduction band (CB) of the QDs. Transient absorption (lambda(pump) = 400 nm, lambda(probe) = 450-750 nm) spectra recorded for Re complex-sensitized CdS and CdS/CdSe composite in the femtosecond time domain revealed a broad transient absorption band in the 580-750 nm region with a peak around 595 nm, and this was attributed to the cation radical formation for Re-complex, either by capturing photoexcited hole from the NCs or by injecting electron to the CB of the NCs. As anticipated, no such spectrum was observed for the CdS/CdTe Re-complex composite system after 400 nm excitation. Electron injection from photoexcited Re-complex to CdS QD and CdS/CdSe core shell was found to be <100 fs, while the hole transfer from photoexcited CdS QD and CdS/CdSe core shell to Re-complex took place within the time scale of 900 fs and 2.5 ps, respectively.